Cell cycle progression data on human skin cancer cells with anticancer synthetic peptide LTX-315 treatment (2020)
ABSTRACT: Skin cancer, including melanoma and non-melanoma (NMSC), represents the most common type of malignancy in the white population [1]. The incidence rate of melanoma is increasing worldwide, while the associated mortality remains stable. On the other hand, the incidence of NMSC varies widely [1,2]. Camilio and collaborators recently described the anticancer properties of LTX-315, a novel synthetic anticancer peptide, commercialized as OncoporeTM [3,4]. Despite various studies demonstrating the efficiency of LTX-315 therapy in inducing cancer cell death, the effects on cell cycle progression of this antitumoral peptide are poorly understood. In this research, we present data about the effect of LTX-315 on the cell cycle of two skin cancer cell lines: epidermoid carcinoma cells (A431) and melanoma cells (A375); as well as on an immortalized normal keratinocyte cell line, HaCaT. Additionally, its cytotoxicity on the cells was determined by measuring the uptake of propidium iodide, in order to establish its relationship with cell cycle progression. The analysed data obtained by flow cytometry show different cell cycle distributions in non-tumoral and skin cancer-derived cell lines in response to LTX-315 treatment. Non-tumoral cells showed a sub-G1 peak, while for tumoral cells there was a shift in the G1peak without producing an obvious distant and distinct sub-G1 peak. This data is in accordance with a major decrease in cell viability in non-cancer cells.